Effect of Combination of Tamsulosin and Tadalafil in Benign Prostate Hyperplasia Patients on International Prostate Symptom Score - Aldeno Wahyu Anandi; Etriyel MYH; Yevri Zulfiqar (HM Publisher, 2022)
Background: Benign prostate hyperplasia (BPH) is the most common pathological condition that contributes to lower urinary tract symptoms (LUTS) in men. Alpha1-blockers are recommended as first-line therapy for LUTS due to BPH (LUTS-BPH). Phosphodiesterase 5 (PDE5-I) inhibitors, which have been used as first-line therapy for erectile dysfunction, have also been found to be effective in treating LUTS-BPH. However, the appropriate combination therapy strategy is still unclear until now. Methods: This study used an experimental design on 17 BPH patients on medical therapy. The patient was given Tamsulosin 0.4 mg monotherapy for 7 days and then continued combination therapy with Tamsulosin 0.4 mg and Tadalafil 5 mg for the next 7 days. Total IPSS score, obstruction, irritation, and quality of life (QoL) were assessed before treatment, after monotherapy, and after combination therapy. Results: The mean age of the research subjects was 62.12 years. Improvements in the total IPSS value, obstruction, irritation, and QoL showed significant changes in both types of therapy compared to the initial value. Combination therapy gave better results than monotherapy, with a mean difference in the decrease in the total IPSS value of 4.41 (p<0.001), obstruction of 3.18 (p<0.001), irritation of 1.41 (p<0.001), and QoL 0.6 (p<0.001). Conclusion: The combination therapy of Tamsulosin 0.4 mg with Tadalafil 5 mg once a day showed clinically and significantly better results than monotherapy in total IPSS, obstruction, irritation, and QoL values in LUTS-BPH patients.